Evaluasi Sistem Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) Di rumah Sakit Umum Daerah Pasaman Barat - Nanda Pariza; Leila Muhelni; Dertha Mukhtar (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Hazardous and Toxic Waste (B3) is a result waste from various activities that contain harmful and toxic materials. According to the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. P.56 of 2015, hospitals are categorized as healthcare facilities required to manage B3 waste. The significance of managing B3 waste in hospitals is substantial, as improper management can lead to various negative impacts. During the management process, particularly during the sorting of B3 waste at the source, there are frequent issues with incorrect packaging and contamination. Such packaging errors during sorting can lead to workplace accidents.The objective of this research is to assess the B3 waste management system at RSUD Pasaman Barat, focusing on whether the processes of sorting, packaging, storage, and transportation comply with Permen LHK No. 56 of 2015, which outlines the procedures and technical requirements for managing hazardous and toxic waste from healthcare facilities. This research employs a qualitative method to evaluate the management system of hazardous and toxic waste (B3). The findings indicate that RSUD Pasaman Barat generates an average of 1,740.51 kg of B3 waste per month. Overall, the processes involved in managing B3 waste at RSUD Pasaman Barat-from sorting and packaging to transportation and temporary storage-still exhibit several non-compliances with Permen LHK No. 56 of 2015.